Implementation Of A Website-Based Recording And Reporting System For Mosque Construction Donations - Rurianto; Yuniar Laeli Nur Faizah; Purwanto (Jurnal Ilmiah Informatika dan Komputer, 2025)
Managing donation funds requires transparency and accountability to maintain trust and ensure proper use of funds. This study aims to implement a web-based fund recording and reporting information system to assist in the efficient and transparent financial management of the Al-Ikhlas Mosque. The problems faced by the Al-Ikhlas Mosque management include manual recording that is prone to loss, miscalculations, and a lack of transparency to residents. To address these issues, a "Website-Based Recording and Reporting System for Development Donations at the Al-Ikhlas Mosque" was developed. The system development method used is the Waterfall method, with stages of analysis, design, implementation, testing, and maintenance. Based on the results of the system trial using Black Box Testing and Likert Scale calculations, the manager received a score of 81.31%, while the community test yielded a score of 81.63%. This information system facilitates management in managing donation funds and facilitates public access to financial reports. Therefore, this information system can be implemented to accelerate and improve the efficiency of the donation fund management process at the Al-Ikhlas Wirasari Mosque.